(untitled) (International Conference on Economics, Finance, Banking and Management, 2025)
This paper explores the linguistic means used to express reproach and criticism in English. Reproach and criticism are essential components of interpersonal communication, often used to regulate behavior, express dissatisfaction, or call attention to errors. However, these expressions are often mitigated or softened due to social norms, politeness strategies, and cultural expectations. The study analyzes both direct and indirect forms of criticism, focusing on their grammatical structures, lexical choices, and pragmatic functions in various social contexts.